2001
DOI: 10.1001/archotol.127.5.497
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Olfactory Impairment on Quality of Life and Disability

Abstract: Patients reporting persistent olfactory impairment after previously documented olfactory loss indicate a higher level of disability and lower quality of life than those with perceived resolution of olfactory compromise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
353
3
18

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 429 publications
(387 citation statements)
references
References 15 publications
13
353
3
18
Order By: Relevance
“…Although the total laryngectomized patients' quality of life tends to be worst in relation to the population in general 24,34 , some studies, in accordance to this research, do not show low scores on the quality of life assessment, compared to the population of not laryngectomized subjects.…”
Section: Discussionsupporting
confidence: 73%
“…Although the total laryngectomized patients' quality of life tends to be worst in relation to the population in general 24,34 , some studies, in accordance to this research, do not show low scores on the quality of life assessment, compared to the population of not laryngectomized subjects.…”
Section: Discussionsupporting
confidence: 73%
“…Lower quality of life is not the only result of olfactory impairment. Miwa et al 31 showed an increased occurrence of disability in this group of patients. In another study, 32 impaired olfaction was a risk factor for certain injuries because normosmia allows early detection and avoidance of potentially hazardous situations, such as cooking or house fires, delayed detection of gas leaks, and exposure to or ingestion of toxic substances.…”
Section: Methodsmentioning
confidence: 65%
“…23 Patients frequently do not discuss their olfaction difficulties; however, the loss of smell can lead to depression and a lower quality of life. [26][27][28][29] Loss of smell can also lead to safety issues and severely altered eating habits and nutritional intake. 30 Resolution of anosmia is unlikely in most cases because the majority of patients with olfaction problems receive from their physician no, unclear, or unsatisfactory information about their diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%